Patient attitudes towards remote memory clinic assessment. (31st December 2021) - Blane, Jasmine; ClareO'Donoghue, M; Craig, Emma; Clarke, Laura; Raymont, Vanessa; Mackay, Clare; Martos, Lola
Abstract: Background: Due to demand on UK memory clinic services, most patients have limited consultant interaction before diagnosis/discharge. Technology offers an opportunity for remote assessment, from telephone/video‐based consultations to fully digitised cognitive assessments with potential to track disease progression. Whilst many acute services utilise remote assessment, there are perceived barriers in memory clinic populations. However, COVID‐19 and related national restrictions may have altered patients' attitudes towards and experience with remote assessment tools. We aimed to investigate attitudes including confidence and perceived challenges towards remote assessment as well as access and experience with technology amongst Oxfordshire memory clinic patients. Method: Between June and September 2020, all patients awaiting initial memory clinic assessment were asked to participate in a standardised semi‐quantitative survey as part of an Oxford Health NHS Foundation Trust service evaluation. Designed with service‐user input, questions aimed to capture availability, experience and confidence using technology and patients' comfort with assessment, diagnosis and future care discussions being conducted remotely, as well as any concerns or comments. Result: Amongst 73 respondents (average age=79.1 years), access to technology was high; 82% reported telephone access and 58% to a laptop, tablet, smartphone or combination of the three. 17% reported previous use of web‐based video conferencing tools, and although confidence using these tools was 7%, this increased with written instruction or relative assistance. Similarly, whilst under half of the respondents felt comfortable with assessments, diagnosis or future care discussions occurring remotely, this increased to approximately two thirds with relative presence (67%, 69% and 66%, respectively). Qualitative analysis of patient's comments regarding remote assessment also revealed concerns over wait times/urgent need for assessment. However, 62% preferred to wait for an in‐person visit, rather than an immediate remote appointment. Conclusion: This survey demonstrates availability of technology in this population but a disparity in willingness to engage in remote assessment. Consequently, there is a need to diverge from one‐size‐fits‐all models to a tiered approach that helps facilitate individual choice based on the availability/confidence with technology and level of relative support. The Oxford Brain Health Centre, an integrated clinical‐research service, provides an opportunity to research this tiered approach in clinical practice.